POSSILITIES OF LIQUID BIOPSY IN THE DIAGNOSIS OF THYROID CANCER - Полион, Никита; Шевченко, Ростислав; Стариков, Владимир (SWorldJournal, 2021)
Thyroid cancer is the most common malignancy of the endocrine system, encompassing a variety of entities with different histologic features and clinics. The diagnosis, therapeutic approach, and follow-up of thyroid cancer demonstrate some controversial as